Combined nevus with dermally located pagetoid cells in the perianal region: a new variant of site-related jistological atypia - Hoffmann, Jochen; Hartschuh, Wolfgang; Flux, Katharina (The American journal of dermatopathology, 2011)
Nevi with site-related histological atypia have been reported in various locations, mainly on the female genitalia, along the anatomical milk line and in skin folds. Therefore, the literature focuses clearly on the atypical nevi of the female genitalia. In the present case, we describe a unique case of a combined perianal melanocytic nevus with architectural and cytologic atypia that differ from the histopathologic features of accepted criteria for atypical genital nevi. A suspicion of malignant melanoma was raised, but few pivotal histological features, the age of the patient and the clinical follow-up for 10 years proved otherwise. This case contributes to the collection of necessary information about perianal nevi that show obvious variations in site-related histological atypia compared with atypical genital nevi. Although the malignant potential of such lesions remains unclear, it is important to prevent overdiagnosis of malignant melanoma with the associated devastating surgery, especially in young patients.